2010
DOI: 10.1007/s11999-009-1133-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Groin Pain After Metal-on-Metal Hip Resurfacing

Abstract: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 33 publications
1
55
3
3
Order By: Relevance
“…Unfortunately, we lacked sufficient statistical power in the current study to adequately address this possibly confounding variable. Recent work examining groin pain after hip resurfacing suggests there is no effect of age on the rate of pain [17]. While female gender has been associated with postoperative groin pain in two studies [17,20], we found no such association.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Unfortunately, we lacked sufficient statistical power in the current study to adequately address this possibly confounding variable. Recent work examining groin pain after hip resurfacing suggests there is no effect of age on the rate of pain [17]. While female gender has been associated with postoperative groin pain in two studies [17,20], we found no such association.…”
Section: Discussioncontrasting
confidence: 76%
“…Recent work examining groin pain after hip resurfacing suggests there is no effect of age on the rate of pain [17]. While female gender has been associated with postoperative groin pain in two studies [17,20], we found no such association. Most hip resurfacings in the present study were performed in men (32 of 39, 82%), limiting our ability to analyze gender as a risk factor.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Studies have used several radiographic, operative, and histopathologic terms to describe the sterile inflammatory reactions reported in patients with MOM and MOP hip implants. The radiographic terms include pseudotumor [35], fluid collection [38], inflammatory bursa [35], inflammatory lesion [15,37], and effusion [2]. Studies described operative appearances as metallosis [6], fluid collection [38], and solid mass [35].…”
Section: Discussionmentioning
confidence: 99%